Studi Komparatif The Day Of The Week Effectmdan The Month Of The Year Effect Dalam Perolehan Return Saham Di Bursa Efek Indonesia Pada Perusahaan LQ 45 Periode Februari 2017-Januari 2018 - Komang Agus Rudi Indra Laksmana; Ni Luh Gede Sri Artika Dewi (Universitas Mahendradatta Denpasar, 2018)
The concept of the efficient capital markets has become a topic of debate is fascinating and quite controversial in the field of finance. Since the introduction his the efficient market hypothesis, comes a variety of behavior of irregularity or discrepancy in the capital markets. Irregularity is referred to as a market anomaly (market anomaly). The Market anomaly that became a lot of attention is the anomalous effect of calendar. These anomalies are the day of the week effect and the month of the year effect. This research was conducted due to the results of several studies that are not consistent on the day of the week effect and the month of the year effect in obtaining the return of shares in Indonesia stock exchange.